Pengaruh Current Ratio dan Firmsize, Terhadap Cash Turn Over Pada Perusahaan Sektor Tekstil dan Garmen - Khoridatul Afifah; Luthfiah Sari (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aimed to determine Current Ratio (CR) and Firm size on Cash turnover ratio (CTO) on textile and garment companies listed on the Indonesia Stock Exchange 2020-2023. This research method used multiple linear regression analysis with data processing using the tools Stata 17 program. The sampling method of this research used a purposive sampling technique. The F-test results showed that simultaneously Current Ratio (CR) and Firm size had a significant effect on Cash turnover ratio (CTO). The T-test results showed that partially, Current Ratio (CR) and Firm size had an effect on Cash turnover ratio (CTO). (Roosmawarni & Mauliddah, 2024)